Ectodermal dysplasia with blindness in sibs on the island of Rodrigues. Issue 5 (May 1992) - Wallis, C E; Beighton, P
Abstract : A brother and sister from the island of Rodrigues had mental retardation, blindness owing to severe ocular malformations, short stature, dysmorphic facial features, hypotrichosis, and dental abnormalities. It is likely that they have a hitherto unrecognised autosomal recessive ectodermal dysplasia syndrome.